A SUPERVISÃO ESCOLAR DO MUNICÍPIO DE SÃO PAULO: DA FUNÇÃO À PROFISSÃO - Teixeira, Angeli Matias (2014)
The overlapping of the administrative over the pedagogical in the everyday routine of the School Supervisor has been having, over the past decades, an important role in the academic discussions. It stems from the dissatisfaction of a great number of these professionals who face a heavy load of burocracy when they take charge and which doesn t allow them to work effectively on the pedagogical projects in the schools. The research in this area, though growing, still needs more attention. The issue of this research focus on the ways the supervisors (in the Rede Municipal de Ensino de São Paulo) handle these two aspects of their role: the administrative, related to the burocracy, and the pedagogical one, related to the educational projects in the schools and other areas of community. This research has as a starting point a historical outline of the path of the School Supervisor in the city, based on the legal material which was responsible for defining this function/position and of the historical background they were a part of. Following that, there s the answers of the research carried out with the School Supervisors from diretorias de ensino regionais de educação of the city analysed in face of the historical background mentioned above and the chosen theoretical guidebooks, in which the works of Demerval Saviani and Celestino Alves da Silva Júnior must be highlighted for these are authors acknowledged as important references and widely cited in the researches concerning the educational supervision area. The research points out important issues to contribute to the understanding of the problems at stake, especially those related to the controversy regarding the duties imposed on the School Supervisor, to the insufficient educational background of these professionals and, therefore, to the difficulty to construct the professional identity of the São Paulo City School Supervisor.